2014
DOI: 10.1039/c4dt02465f
|View full text |Cite
|
Sign up to set email alerts
|

Facile tandem Suzuki coupling/transfer hydrogenation reaction with a bis-heteroscorpionate Pd–Ru complex

Abstract: Design and synthesis of the bis(pyrazol-1-yl)methane based bis-heteroscorpionate Pd-Ru complex results in efficient tandem Suzuki coupling/transfer hydrogenation reaction with a broad range of substrate reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…These findings may suggest that in alcoholic media and at high alkoxide concentrations (NaOiPr, KOtBu), complex 3 mainly catalyzes dehalogenation and further TH reactions, in accordance with other bimetallic Pd-Ru systems [5,6,10,16,17]. Conversely, when the alkoxide Reaction conditions: Ketone (1 mmol), NaOiPr (0.05 mmol, 5 mol%), 3 (0.05 mol%) or 1 (0.1 mol%), 2-propanol (10 mL), 100°C.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…These findings may suggest that in alcoholic media and at high alkoxide concentrations (NaOiPr, KOtBu), complex 3 mainly catalyzes dehalogenation and further TH reactions, in accordance with other bimetallic Pd-Ru systems [5,6,10,16,17]. Conversely, when the alkoxide Reaction conditions: Ketone (1 mmol), NaOiPr (0.05 mmol, 5 mol%), 3 (0.05 mol%) or 1 (0.1 mol%), 2-propanol (10 mL), 100°C.…”
Section: Resultssupporting
confidence: 60%
“…For the Suzuki-Miyaura/transfer hydrogenation transformation entailing C-C and C-H bond forming reactions, catalysts are mainly based on heterogeneous systems [4,10] and enzymes [11][12][13][14][15]. By contrast, homogeneous bimetallic catalysts for this tandem reaction are less common [3,5,16,17], and some of them display higher activity compared to the combination of the single monometallic species [5,17]. Therefore, the design of novel heterobimetallic complexes based on suitable ligands is crucial to achieve more efficient catalysts for tandem reactions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The same authors expanded the use of bis‐heteroscorpionate ligand IVc to obtain homometallic dipalladium(II) complex [(PdCl 2 ) 2 (µ‐ IVc )] ( 111 ), and also the heterometallic Ru‐Pd derivative [{( p ‐cym)RuCl}(µ‐ IVa )PdCl 2 ](ClO 4 ) ( 112 ). The formation of the heterodimetallic complex was confirmed by X‐ray diffraction studies, which showed that the palladium centre has a distorted square‐planar geometry and the ruthenium a piano‐stool geometry.…”
Section: Ligands Of Type IV and Vmentioning
confidence: 99%
“…Tetra(pyrazolyl)derivatives were successfully used for preparation of coordination polymers and molecular complexes [11][12][13][14][15]. In our preceding studies we have developed a synthetic procedure for the simplest bitopic tetra(pyrazolyl)derivative -1,1,2,2-tetra(pyrazol-1-yl)ethane [16] and determined the crystal structure of its copper(II) molecular complex [17].…”
Section: Introductionmentioning
confidence: 99%